HBV Viral Load and Liver Enzyme Levels May Be Associated with the Wild MBL2 AA Genotype - Tuane Carolina Ferreira Moura; Ednelza da Silva Graça Amoras; Mauro Sérgio Araújo; Maria Alice Freitas Queiroz; Simone Regina Souza da Silva Conde; Sâmia Demachki; Rosimar Neris Martins-Feitosa; Luiz Fernando Almeida Machado; Izaura Maria Vieira Cayres-Vallinoto; Ricardo Ishak; Antonio Carlos Rosário Vallinoto (Hindawi Limited, 2017)
The present study investigated the frequencies of rs1800450 (MBL ⁎B, G>A), rs1800451 (MBL ⁎C, G>A), and rs5030737 (MBL ⁎D, C>T) polymorphisms in exon 1 of the MBL2 gene among patients with chronic viral hepatitis. Blood samples from patients infected with hepatitis B virus (HBV; n=65), hepatitis C virus (HCV; n=92), and a noninfected control group (n=300) were investigated. The presence of polymorphisms was detected using a real-time polymerase chain reaction to correlate with liver disease pathogenesis and fibrosis staging according to the Metavir classification. The genotypic and allelic frequencies showed no significant differences between the groups, but patients with active HBV and the wild AA genotype presented a positive correlation between increased transaminase and HBV DNA levels and the presence of mild to moderate fibrosis. Patients with HCV and the wild AA genotype presented mild inflammation and higher HCV RNA levels, although the same association was not observed for the fibrosis scores. The results suggest that the mutations in exon 1 of the MBL2 gene do not contribute directly to the clinical and laboratory features of HCV and HBV infections, but further studies should be performed to confirm whether the wild AA genotype has indirect effect on disease progression.